Brazil : Report on Observance of Standards and Codes (ROSC)-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides an assessment of fiscal transparency practices in Brazil. The authorities have completed the fiscal transparency questionnaire prepared by the IMF staff. The assessment has two parts that are discussed in this study. In the first part, descriptions of practice, prepared by the IMF staff on the basis of the questionnaire response and additional information provided by the authorities are discussed. In the second part, an IMF staff commentary on fiscal transparency in Brazil is presented. Brazil uses very comprehensive fiscal definitions.